Revealing dynamic-mechanical properties of precipitates in a nanostructured thin film using micromechanical spectroscopy - Markus Alfreider; Michael Meindlhumer; Tobias Ziegelwanger; Rostislav Daniel; Jozef Keckes; Daniel Kiener (MRS Bulletin, 2024)
Nanostructured materials with their remarkable properties are key enablers in many modern applications. For example, industrial dry-milling processes would not be as widely spread without the use of hard, wear-resistant metal nitride coatings to protect the cutting tools. However, improving these nanostructured thin films with regard to dynamical properties is demanding as probing respective parameters of (sub-)micron layers without any substrate influence is still challenging. To extend the scientific toolbox for such spatially confined systems, a novel methodological approach based on resonance peak measurements of a cantilever-transducer system termed micromechanical spectroscopy (µMS) is developed and applied to a Al0.8Cr0.2N model system. The mainly wurtzite type supersaturated Al0.8Cr0.2N system showed precipitation of cubic CrN at grain boundaries and local Cr variations upon annealing at 1050°C. This was accompanied by an increase in the previously unknown damping capability of 63 percent and an increase in Young’s modulus by 36 percent.
Publisher Copyright: extcopyright 2023, The Author(s).
Keywords: AlCrN; Dynamic testing; Grain-boundary segregation engineering; Heat treatment; Micromechanical testing; Precipitation